Territoires et ressources des sociétés néolithiques du Bassin Parisien : le cas du néolithique moyen (4500-3800 av. n. è.) - Lietar, Claira, (Archaeopress Publishing Ltd, 2017)
The aim of this book is to study forms of territorial patterning and resource management in the middle Neolithic I and II, between 4500 and 3800 BC in the Paris basin.